Determinación del costo de producción en la industria del mueble del señor Segundo Marcelo Buele Sarango, de la ciudad de Machala, provincia de El Oro, periodo julio – agosto del 2014 - Romero Gálvez, Yaricsa del Rocío (2015)
The presentresearch onDETERMINING THECOST OFPRODUCTIONINTHE FURNITURE INDUSTRYOF THE LORDSECONDMARCELOBUELESARANGO, MACHALACITY, PROVINCE OF GOLD,PERIODJULY -AUGUST2014, was based onthe need to providethis companya system thatallows the control anduse ofthe cost elementsthat are usedduring the production process, allowing for maximumoptimization anduse thereofin the manufacture offurniture,the generation ofreliable and timelyinformationforproductive activitiescostingin order to knowhow muchI costto produce inthe company. Allobjectiveswere metby applying thecostaccounting processforproduction ordersfor whicha plan andmanualwas developedaccounts, inventory of goods toJuly 1, 2014was determined, documents are designedto controlmaterials, labor andmanufacturing overhead costs, thecost sheetconstitutedan effective toolfor determining thevalue-priced hererecordedthreecost elementswhose resultswere transferred to thejournalin whichthe utility isdeterminednetgenerated inthe study period. At the end ofthis paperthe respective conclusionsandrecommendations were developed, among the most importantwe can mention theproper controlof costs throughthe implementation ofcost sheetin order to havea propermanagement ofits elementsand determinethe unit costandtotal for eachfinished product,enough for theownerdefinitelyacceptthis system forcost controlreasonsyour company